Sistem Pendukung Keputusan Penentuan Mahasiswa Lulusan Terbaik Menggunakan Metode Analitycal Hierarchy Process Pada Perguruan Tinggi - R. Mahdalena Simanjorang (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
This study discusses the determination college students the best graduates, the process of determining college students the best graduate is a problem that involves many criteria being assessed, so in the completions required of the decision support system. The process of determining the best graduates students at University is still constrained because there is no effective method and the assessment criteria are only aware of the value of IPK.In designing this system, researchers use Analytical Hierarchy Process (AHP) method as the weighting method used.Four basic criteria used are ipk value, scientific papers, outstanding achievements / capabilities and English. The AHP method can display the priority value of the criteria that can be used as an alternative to determine the best graduate student. Application of decision support system determination of the best graduate students is made with desktop-based programming language that is Visual Basic 2010 and MySQL as the database. The built system is able to provide a rating recommendation of the number of values sorted by the highest weight. With this system is expected to provide an alternative for decision makers to determine the best graduate students at University